Digital Economy for Africa : Country Diagnostic of Senegal - World Bank Group (World Bank, Washington, DC, 2019)
The rapid technological advancement is now disrupting the global economy and creating new business and development models, offering countries opportunities to leapfrog over traditional paths for economic growth. Over the past years, digital technologies have been spreading throughout the world at a faster pace than previous waves of technological innovation, re-shaping consumer behavior, social interaction, businesses and governments. The digital economy (DE), which encompasses a wide range of new applications of information technology in business models and products, can spur economic growth, productivity and employment and, with appropriate policies to mitigate inherent risks, has a potential to support inclusive outcomes. In this global context, digital transformation of the economy has become a major objective for the government of Senegal (GoS). This report provides a snapshot of the state of DE in Senegal and uses several World Bank tools and international best practices to provide actionable recommendations to the GoS.